2019
DOI: 10.1016/j.amepre.2018.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Smoke-Free Policies and Cessation Programs Among U.S. Working Adults

Abstract: Introduction: Workplace tobacco control interventions reduce smoking and secondhand smoke exposure among U.S. workers. Data on smoke-free workplace policy coverage and cessation programs by industry and occupation are limited. This study assessed smoke-free workplace policies and employer-offered cessation programs among U.S. workers, by industry and occupation. Methods: Data from the 2014–2015 Tobacco Use Supplement to the Current Population Survey, a random sample of the civilian, non-institutionalized pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…The industry subcategories with the highest prevalences of reported SHS exposure in this study and the industry category with the highest number of exposed workers (construction) include outdoor workplaces and other settings that are unlikely to be protected by smoke-free laws. A recent study determined that indoor workers who reported working at a worksite having a 100% smoke-free policy had significantly lower odds of smoking combustible tobacco than did those reporting a partial or no smoke-free policy ( 9 ). Enhanced and sustained efforts to protect nonsmoking workers through comprehensive smoke-free laws and implementation of smoke-free workplace policies by employers can benefit public health.…”
Section: Discussionmentioning
confidence: 99%
“…The industry subcategories with the highest prevalences of reported SHS exposure in this study and the industry category with the highest number of exposed workers (construction) include outdoor workplaces and other settings that are unlikely to be protected by smoke-free laws. A recent study determined that indoor workers who reported working at a worksite having a 100% smoke-free policy had significantly lower odds of smoking combustible tobacco than did those reporting a partial or no smoke-free policy ( 9 ). Enhanced and sustained efforts to protect nonsmoking workers through comprehensive smoke-free laws and implementation of smoke-free workplace policies by employers can benefit public health.…”
Section: Discussionmentioning
confidence: 99%
“…First, because we used a convenience sampling approach, the distribution across certain variables in our sample may not mirror national data. Tobacco use was over-represented in our sample compared with national data, 35 as were indoor workers 34 and those intending to quit vaping in the next 6 months. 20 The study was not designed to sample industries in a representative way, and so differences between industries should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 84%
“…These findings are consistent with national data that show 27.2% of all working adults reported having an employer-sponsored cessation program. 34 There was notable variability in the presence of vaping cessation support by industry. Those in health services and manufacturing were the most likely to indicate a quit vaping program was in place, while those in retail and government/non-profit were the least likely.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research using TUS-CPS data from 1998–2002 (before the widespread implementation of smoke-free laws) found that women with lower income levels were less likely to report smoke-free policies in their workplaces, compared to women with higher incomes [9]. A study using data from the 2014–2015 wave of the TUS-CPS also found that the proportion of workers reporting coverage by a 100% smoke-free policy was lowest among individuals with an annual household income <$35,000, compared to individuals at higher income levels [27]. An avenue for future research could be to investigate whether the impact of legislated smoking restrictions on cessation is stronger in contexts where voluntary policies are less prevalent, as in many countries that rapidly adopted policies recommended by the Framework Convention on Tobacco Control (FCTC).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of literature has elaborated on the potential for spurious results associated with multiple comparisons [31,32]. In addition, we did not consider the extent to which smoke-free policies may have been introduced alongside other cessation support services, particularly in workplaces [27]. While outside of the scope of this study, such cessation services, including counseling and self-help materials, may impact the relationship between smoke-free policies and cessation.…”
Section: Discussionmentioning
confidence: 99%